Efficacy of Topical Compound Danxiong Granules for Treatment of Dermatologic Toxicities Induced by Targeted Anticancer Therapy: A Randomized, Double-Blind, Placebo-Controlled Trial. (6th August 2017) - Tian, Aiping; Zhou, Aiping; Bi, Xinyu; Hu, Shangying; Jiang, Zhichao; Zhang, Wen; Huang, Zhen; Shi, Hongzhe; Yang, Boyan; Chen, Wei
Abstract : Dermatologic toxicities resulting in dose reduction or discontinuation of treatment pose challenges for targeted anticancer therapies. We conducted this randomized, double-blind, placebo-controlled trial to investigate the efficacy of topical application of Compound Danxiong Granules (CDG) for treatment of dermatologic toxicities associated with targeted anticancer therapies. One hundred and ten patients with dermatologic toxicities induced by targeted anticancer therapies were randomly assigned to CDG or placebo group. Each crude herb ( Rhizoma Chuanxiong, Paeonia suffruticosa Andr., Cortex Phellodendri, Geranium sibiricum L., and Flos Carthami ) was prepared as an instant herbal powder. Application of the CDG via topical washes lasted 20 minutes, twice daily, for 10 days. The primary outcome was the total effective rate, defined as reduction in at least one grade of skin toxicity. The total effective rate was 77.61% (52/67) in the CDG group and 27.27% (9/33) in the placebo group (P < 0.0001 ). Compared to the placebo treatment, CDG treatment achieved a higher total effective rate for hand-foot skin reaction (95.45% versus 27.27%), acneiform eruption (69.23% versus 30.78%), and paronychia (68.42% versus 22.22%). Topical application of CDG can effectively attenuate dermatologic toxicities induced by targeted anticancer therapies. The effect of CDG was more pronounced in hand-foot skin reaction.